The Relationship Between Direct Foreign Capital Investment, Economic Freedom And Economic Growth In Emerging Markets - Murat Akkaya (Selçuk Üniversitesi Sosyal Bilimler Meslek Yüksekokulu Dergisi)
Economic growth is defined as an increase in the volume of production of an economy over time. Economic growth is important for the country at every level of development. Foreign capital investments are generally divided into two categories: direct foreign capital investments and indirect foreign capital investments. Foreign direct investment flows in developing markets are seen as the main driving force of economic development, employment and national income. With globalization, there have been significant increases in Foreign Direct Investment since 1990s. Despite the fact that the foreign direct investment (FDI) inflows predicts tremendous benefits to the host country, there are conflicting results in the FDI - growth relationship in the literature. The aim of this study is to analyze the relationship between direct foreign investment, economic freedom and economic growth in the 12 countries defined as emerging markets in the period of 1995-2016 by using dynamic panel data method. According to the results of the analysis, there is a relation between FDI and economic growth. Also no relation with economic freedom has been observed. Moreover, high technological product exports and population affect FDI. There is no relation between FDI and trade openness, interest rates, unemployment rate, domestic consumption.